Adolescent reinforcement sensitivity as a longitudinal predictor of psychopathology: investigating inhibitory control and emotion regulation as underlying mechanisms - Izadpanah, Shahrzad; Barnow, Sven (2017)
Prevention and treatment of mental health problems are considered as two major aims of clinical psychological research. Designing prevention programs requires empirical studies that shed light on the risk factors underlying the development of psychopathology that need to be integrated as intervention targets. The current dissertation focuses on personality traits and emotion regulation (ER) as two key elements of theoretical models explaining the development of anxiety and depression. In the first part of this dissertation, the concepts of ER and reinforcement sensitivity are explained and the aims of the dissertation are further clarified. The first two studies investigate adolescent reinforcement sensitivity as a longitudinal risk factor for psychopathology symptoms. The differentiating effects of punishment and reward sensitivity on various psychopathology symptoms are highlighted. In order to understand the underlying mechanism of this link, the indirect effects of ER (Study 1) and anger rumination (Study 2) on this link are examined. Results show that punishment sensitivity leads to an increased use of maladaptive ER which in turn increases the risk for development of psychopathology. The Study 3 takes one step back to examine inhibitory control as an underlying mechanism of the punishment sensitivity and ER link. The findings provide some support for the hypothesis that punishment sensitivity contributes to the habitual use of maladaptive ER through inducing attentional control deficit. In general, results suggest that punishment sensitivity and maladaptive ER constitute vulnerability for development of mental health problems. Therefore measurement of individual differences in reinforcement sensitivity and targeting ER among those with high levels of punishment sensitivity seems to be a promising pathway for reducing the risk for development of psychopathology. Further, our results suggest that targeting attentional control might have protective effects against the development of maladaptive ER strategies. Finally, the findings are discussed and summarized and the implications and directions for future research are highlighted.
Publication-based thesis
Keywords: Hochschulschrift